A COMPARATIVE ANALYSIS OF HUMAN RESOURCE POLICIES AND PRACTICES ON EMPLOYEE PERFORMANCE AND SUSTAINABILITY OF HOTEL ORGANISATIONS IN BOTSWANA - Manhotoma, Mercy G.; Mahachi, Delly (European Scientific Journal, ESJ, 2014)
The main aim of this study is to identify current human resources management (HRM) policies and practices at two prominent hotels in Gaborone. To achieve this aim, a mixed method approach in data collection and analysis was adopted. Questionnaires and interviews were administered to a sample of fifty four employees who were purposively selected from the two hotels. In addition, interviews were held with five senior level managers at the respective hotels. Major findings reveal that the majority of the employees were not satisfied with policies that address employee reward systems. However most lower level operational staff perceived that their own goals, attitudes and perceptions could be maximized by receiving recognition for best performance, striking a balance between personal and business aspects, avoiding personal interests on the job and fostering increased communication between management and employees. Furthermore it was found out that employees supported company policies that ensured that employee efforts are supported by management. This study, in conclusion emphasizes the need for hotels to exercise fair reward and motivation systems for their staff.